Combination of alpha-melanocyte stimulating hormone with conventional antibiotics against methicillin resistant Staphylococcus aureus. - Madhuri Singh (Public Library of Science (PLoS), 2013)
Our previous studies revealed that alpha-melanocyte stimulating hormone (α-MSH) is strongly active against Staphylococcus aureus (S. aureus) including methicillin resistant S. aureus (MRSA). Killing due to α-MSH occurred by perturbation of the bacterial membrane. In the present study, we investigated the in vitro synergistic potential of α-MSH with five selected conventional antibiotics viz., oxacillin (OX), ciprofloxacin (CF), tetracycline (TC), gentamicin (GM) and rifampicin (RF) against a clinical MRSA strain which carried a type III staphylococcal cassette chromosome mec (SCCmec) element and belonged to the sequence type (ST) 239. The strain was found to be highly resistant to OX (minimum inhibitory concentration (MIC) = 1024 µg/ml) as well as to other selected antimicrobial agents including α-MSH. The possibility of the existence of intracellular target sites of α-MSH was evaluated by examining the DNA, RNA and protein synthesis pathways. We observed a synergistic potential of α-MSH with GM, CF and TC. Remarkably, the supplementation of α-MSH with GM, CF and TC resulted in ≥ 64-, 8- and 4-fold reductions in their minimum bactericidal concentrations (MBCs), respectively. Apart from membrane perturbation, in this study we found that α-MSH inhibited ≈ 53% and ≈ 47% DNA and protein synthesis, respectively, but not RNA synthesis. Thus, the mechanistic analogy between α-MSH and CF or GM or TC appears to be the reason for the observed synergy between them. In contrast, α-MSH did not act synergistically with RF which may be due to its inability to inhibit RNA synthesis (<10%). Nevertheless, the combination of α-MSH with RF and OX showed an enhanced killing by ≈ 45% and ≈ 70%, respectively, perhaps due to the membrane disrupting properties of α-MSH. The synergistic activity of α-MSH with antibiotics is encouraging, and promises to restore the lost potency of discarded antibiotics.